Model of Healthy Personality in Islamic Aspect - Rajabov, Elvin (Scholarya Demo Journal of Ruby, 2020)
Throughout history, the subject of a healthy personality has attracted psychologists, philosophers, moral and religious scholars. Psychologists have suggested different and specific theories about personality formation, the factors influencing it and characteristics of a healthy personality. There is also a healthy personality model suggested by Islam, just as there is a healthy personality model that other religions propose. This article first discusses theories of different schools of psychology to explain personality. Further, the characteristics of a healthy personality model in the Islamic aspect were also investigated. The first part of the article outlines theories of various psychological schools on personality. From these theories, psychodynamic theories, which are the theories of the main representatives of psychoanalysis school, have been studied. Then, humanistic theories of personality including theories of Abraham Maslow, Carl Rogers, Cordon Alport are explained. This section also outlines the theories of behavioral and cognitive schools about personality. These theories deal with different theories of psychologists about personality formation, the factors that influence it and the causes of personality problems. The second part of the article explores a healthy personality model in the Islamic aspect. This section describes the characteristics of a healthy personality according to Islamic guidelines. It also explores the notions that are mentioned in the Holy Quran close to personality. This section also mentions people who are exemplified for raising a healthy personality in Islamic sources. In addition, the Islamic aspect of a healthy person’s attitude towards existence, himself and others is explored.